(untitled) (Philology, 2026)
The term Columbian exchange refers to the migration of various plants, animals, people, and ideas between the Old and the New World. The article comments on the impact of this phenomenon on the European and, in particular, Bulgarian agriculture and cuisine. The spread of a number of crop plants and their names is traced.